Kampung Pelangi Semarang As Spectacle of City Landscape - Christanti, Sherley Ika (Publikasi Indonesia, 2023)
Kampung Pelangi is one of the trends used to dress up several villages in Indonesia so that they have selling points to help the community develop more in advancing their villages. The villages that become Pelangi villages have quite similar types of village problems, namely villages that are densely populated with the majority of the population being the lower middle class. This kelurahan is located by the river and has a hillside site and is in the center of the city. This gave rise to a phenomenon where an urban village became an object of public spectacle. Coupled with easy digital access to promote goods for sale, including the beauty of the village, this has made the village an object to be watched and enjoyed rather than simply defined as a place to live. What is witnessed or shown is a scenario planned by the community and the village government, by looking for the potential that exists in people's lives, then raised and highlighted as the attraction of the village spectacle. This paper discusses how Kampung in Indonesia developed within the scope of the city of Semarang and ended up becoming a trend of dressing up as a village in the modern era with the case study of Kampung Pelangi to reveal the extent to which the level of spectacle created in reality in urban areas. villages in Indonesia seen from the Kampung Pelangi phenomenon.